How can a superficial appearance become deeply ingrained? Focusing on the cultural relationship between the spread of Christianity in China and three modern plays including The Divine Light - HAN, Han (Journal of Research for Christianity in China (JRCC), 2025)
This article discusses the relationship between Christianity diffusion in China and classical dramas, 《灵光》、《雷雨》and 《青龙潭》.after a series of analysis, the author has a conclusion that , In the modern academic history of different times, there are many different reaction of Christianity spirit., in fact, the Christianity has a positive effective to Chinese modern drama. Also, Christianity diffusion pushed industry of Chinese modern drama.